2021
DOI: 10.1177/21582440211056614
|View full text |Cite
|
Sign up to set email alerts
|

Web Accessibility of the Top Research-Intensive Universities in the UK

Abstract: Although the web accessibility of universities around the world is well documented, much remains unknown about this aspect of higher education institutions in the UK. Using three automated web accessibility tools (TAW, WAVE and EIII Page Checker), this study explores the accessibility of the homepages of 66 research-intensive universities with respect to the WCAG 2.0 checkpoints. The results show that the most common checkpoint violations involve the provision of text alternatives for non-text content, contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The study of Alim [4] explored the accessibility of the home pages of 66 research-intensive universities in the UK. Three automated tools have been used: WAVE, TAW, and EIII.…”
Section: Related Workmentioning
confidence: 99%
“…The study of Alim [4] explored the accessibility of the home pages of 66 research-intensive universities in the UK. Three automated tools have been used: WAVE, TAW, and EIII.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed that only four public institution websites and only one private institution website had no errors and were completely accessible to their users. In a recent case study by Ismail and Kuppusamy [22], 44 college websites were investigated, and major accessibility issues were identified using TAW and aXe tools. Authors listed the major accessibility barriers reported by websites in terms of several identified problems, warnings, and success criteria violations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Web Content Accessibility Guidelines are organized under four principles: perceivable, operable, understandable, and robust [12]. [12].…”
Section: Four Principles Of Web Accessibilitymentioning
confidence: 99%